ANAK PELAKU TINDAK PIDANA PERSETUBUHAN BERDASARKAN UNDANG-UNDANG PERLINDUNGAN ANAK (PUTUSAN No.7/PID.SUS-ANAK/2020/PN.MBN) - Nurul Kamila; Vientje Ratna Multiwijaya (Reformasi Hukum Trisakti, 2022)
The crime of child sexual intercourse and abuse is regulated specifically in Law number 35 of 2014 Article 76D concerning Child Protection. It explains that each individual is not justified in committing violence or sending threats of violence and forcing child to have sex with him or with another individual. The research’s problems: is the action of a child who commits crime of intercourse are in accordance with Article 81 (2) of Law number 17 of 2016 concerning Child Protection (Decision No.7/Pid.Sus- Anak/2020/PN.Mbn) and whether the prison sentence imposed on perpetrator meets sentencing requirements in Law number 11 of 2012 concerning Juvenile Criminal Justice System. The research object is decision number 7/Pid.Sus-Anak/2020/PN.Mbn and the research is a normative and descriptive analytical legal research, using secondary data obtain through library research, analyzed qualitatively and conclusions are drawn using inductive method. The research’s conclusions: The actions of child perpetrators in the crime of intercourse are inappropriate if they only use Article 81 (2), but must also be based on Article 81 (1) of Law number 17 of 2016 concerning Child Protection, Punishment of the Child Defendant is in accordance with Law number 11 of 2012 but should not be given additional punishment.